Current State of Resistance to Antibiotics of Last-Resort in South Africa: A Review from a Public Health Perspective - Osei Sekyere, John (Frontiers in Public Health, 2016)
A review of the literature was undertaken to delineate the current level and mechanisms of resistance to carbapenems, colistin, and tigecycline in South Africa. Thirty-two English publications and 32 National Institute of Communicable Diseases communiqués identified between early January 2000 and 20 May, 2016 showed substantial reports of NDM (n = 860), OXA-48 (n = 584), VIM (n = 131), and IMP (n = 45) carbapenemases within this period, mainly in Klebsiella pneumoniae (n = 1138), Acinetobacter baumannii (n = 332), Enterobacter cloacae (n = 201), and Serratia marcescens (n = 108). Colistin and tigecycline resistance was prevalent among K. pneumoniae, A. baumannii, S. marcescens, and E. cloacae. The first mcr-1 colistin resistance gene to be detected in South Africa was reported in Escherichia coli from livestock as well as from hospitalized and outpatients. There are increasing reports of NDM and OXA-48 carbapenemases among Enterobacteriaceae and A. baumannii in South Africa. Mcr-1 is now present in South African patients and livestock. Resistance to carbapenems, colistin, and tigecycline restricts infection management options for clinicians.